Two new species of the genus Bhatia (Hemiptera: Cicadellidae) from south India with new locality records of other species - Viraktamath, C. A.; Murthy, M. Shankara (Zootaxa, 2009)
Bhatia radhamaniae sp. nov. (Karnataka: Sirsi) and Bhatia serrata sp. nov. (Kerala: Nilambur) are described and illustrated. The genus Bhatia is redefined. A key to species of Bhatia from the Indian subcontinent is also provided. New locality records for Bhatia distanti Zhang & Webb, Carvaka kumari Viraktamath, Indokutara conica Viraktamath, Kotabala adiveyyai Viraktamath and Parohinka longiseta (Melichar) are given.